(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
The reliability and stability of modern electric power systems largely depend on the effectiveness of protection and control equipment. Microprocessor-Based Protective Relay (MPR) systems have become an essential component of modern power networks due to their high accuracy, flexibility, and capability to process electrical signals in real time. One of the most important tasks of protective relays is the continuous monitoring and analysis of current and voltage signals under both normal and fault operating conditions.